Fears of Social Decline in Germany: Magnitude and causes in times of growing right-wing populism - Bettina Kohlrausch (Hans-Böckler-Stiftung, 2018)
The right-wing populist party AfD's victory in the last parliamentary election raises the question of the causes of social uncertainty and fears of social decline. Uncertainty involves a concern about maintaining social status and extends well into the middle classes. In the lower social strata, fears of social decline can be explained by a difficult economic situation. Yet social uncertainty is also prevalent among individuals who are not directly threatened by social decline. This can be accounted for by the fact that fears of social decline are also based on a perception of helplessness, especially within the context of work. The AfD capitalizes on this rather vague feeling of general social uncertainty.
urn:nbn:de:101:1-2019022610351346794902
Keywords: 300; social uncertainty; fear; social decline